2018
DOI: 10.22259/2639-1783.0101005
|View full text |Cite
|
Sign up to set email alerts
|

Caregiving for Children Living with Disability in the Informal Settlements in Kenya: Exploring the Social Experiences of the Urban Poor Living in Mukuru Slums in Nairobi

Abstract: Caregivers are entrusted with provision of the needs of those who are incapacitated by disabilities in the society. However they face many challenges in the process of caregiving. Understanding the experiences of caregivers would be instrumental in addressing the challenges faced in the process of caregiving. The study investigated the social experiences of caregivers of children living with disability. The study was guided by Friedman's social (dis) empowerment which highlights 8 areas of (dis) empowerment du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…According to Alm-Roijer et al (2014), therapists need to continuously build on their knowledge to enhance their understanding of the importance of the therapy process and the benefits of being consistent in attending sessions. Availability of inadequate resources, especially monies, has been a significant hindrance in ensuring that therapists repeatedly gain access to capacity-building chances, especially in informal villages in Kenya, which limits their efficiency in delivering treatment (Ndirangu & Midigo, 2019). The current study, therefore, will find out how therapyrelated constraints affect the delivery of SLT services to children with CP in Kibra Slums, Nairobi City County, Kenya.…”
Section: Empirical Studies and Knowledge Gapsmentioning
confidence: 99%
“…According to Alm-Roijer et al (2014), therapists need to continuously build on their knowledge to enhance their understanding of the importance of the therapy process and the benefits of being consistent in attending sessions. Availability of inadequate resources, especially monies, has been a significant hindrance in ensuring that therapists repeatedly gain access to capacity-building chances, especially in informal villages in Kenya, which limits their efficiency in delivering treatment (Ndirangu & Midigo, 2019). The current study, therefore, will find out how therapyrelated constraints affect the delivery of SLT services to children with CP in Kibra Slums, Nairobi City County, Kenya.…”
Section: Empirical Studies and Knowledge Gapsmentioning
confidence: 99%
“…Regardless of the influence culture has on caring for CLD in Africa, the implications of CRS are the same across all countries. Ndirangu and Midigo ( 2019 ) in a study conducted in Kenya revealed that CCLD unquestionably face more huddles than caregivers of children without disabilities, which subsequently puts more strain on their caregiving role. Masulani‐Mwale et al ( 2016 ) supported this assertion in a study conducted in Malawi, in which the CRS experienced by parents of CLD is a result of several hitches, such as stigma, suicidal ideas, inaccessibility to support services for themselves and their children, and some even reporting to have had advises from their neighbours to kill their CLD.…”
Section: Introductionmentioning
confidence: 99%